Does earning management affect financial distress? Evidence from state-owned enterprises in Indonesia - Nur Sayidah; Aminullah Assagaf; Zulfikar Faiz (Cogent Business & Management, 2020)
Financial distress in state-owned enterprises(SOEs) becomes a problem needing attention. This study aims to analyze the effect of earnings management, marketing productivity, and government subsidies on financial distress of SOEs with firm size as a control variable. The sample consisted of 19 state-owned companies receiving government subsidies and state capital participation in 2015-2017. The data analysis method used was a quantitative approach. The results showed that marketing productivity affected financial distress in state-owned companies receiving government subsidies in 2015-2017. High marketing productivity showed that SOEs were achieving high sales to meet public demand. Furthermore, earning management and subsidy had no effect on financial distress in state-owned companies. SOEs management performed earnings management within a certain limit so that it did not affect financial distress.
Keywords: 650; Earning management; financial distress; marketing productivity subsidies